Studi Interaksi Obat dan Reaksi Obat Merugikan pada Pasien HIV/AIDS dengan Koinfeksi Tuberkulosis di RSUP Dr. Hasan Sadikin Bandung - ALEXANDRA VANIA ANDI; LIA AMALIA; RUDI WISAKSANA (JURNAL ILMU KEFARMASIAN INDONESIA, 2015)
HIV/AIDS and tuberculosis require combination therapy that can lead to drug interactions and unwanted drug effects or adverse drug reactions (ADRs). This study was aimed to determine the potential drug interactions, estimate the occured ADRs and provide treatment recommendations for HIV/AIDS patients with tuberculosis. This research was a descriptive study which was conducted retrospectively in forty eight HIV/AIDS patients with tuberculosis receiving treatments in the Teratai clinic, Dr. Hasan Sadikin Bandung Hospital in 2013. From these forty eight patients, there were 109 incidences of potential drug interactions with major significance, 299 incidence of with moderate significance and 58 with minor significance. Estimated ADRs with the greatets number found in this study was 8 incidences of gastrointestinal disorders, 5 incidences of drug eruption, 5 drug-induced liver injury (DILI) incidences and 4 peripheral neuropathy incidences. Patients receiving category 1 tuberculosis therapy was recommended to use tenofovir, lamivudine, and efavirenz as antiretroviral therapy, whereas patients receiving category 2 tuberculosis therapy was recommended to use zidovudine, lamivudine, and efavirenz.